Pengaruh Citra Merek, Kualitas Produk Terhadap Keputusan Pembelian Sepatu Olahraga Ortuseight di Soccer Corner Bandar Lampung - Riduan; Faridaefriyanti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
In the modern era, sports have become an essential need for individuals as it helps maintain health and reduce the risk of various diseases that can hinder daily activities. Additionally, sports serve as a way for people to spend their leisure time amidst their busy schedules. Companies in the sports industry strive to be market leaders by offering high-quality products. This research aims to analyze the influence of brand image and product quality on the purchasing decisions of Ortuseight sports shoes at Soccer Corner, Bandar Lampung. This study uses a quantitative method with a sample of 45 respondents. The analytical techniques used include classical assumption tests and multiple linear regression. The results indicate that brand image has a 16.72% influence on purchasing decisions, while product quality has a 23.06% influence. Brand image and product quality together influence purchasing decisions by 17.3%. Both variables significantly impact and mutually influence each other.